Impacts of ownership structure on stock price synchronicity of listed companies on Vietnam stock market - Nghia Phan Trong; Vu Thi Thuy Van (Cogent Business & Management, 2021)
The purpose of this paper is to examine the impacts of ownership structure on stock price synchronicity in Vietnam stock market. The research has been conducted with a sample of all of those companies listed on Vietnam stock market from 2007 to 2017 and used the multivariate regression method with array data sets. The research findings have shown that in Vietnam, stock price synchronicity is mainly caused by general information of the whole market. In addition, the paper has pointed out that a negative relationship exists between the ownership of large shareholders, the ownership of foreign investors and the stock price synchronicity and that there is a positive relationship between state ownership and the stock price synchronicity. The research findings have indicated more clearly the phenomenon of stock price synchronicity in a developing country and offered corporate executives several important implications to limit synchronicity and enhance the informativeness in the company's stock price.
Keywords: 650; Ownership of large shareholders; ownership of foreign investors; stock price synchronicity; Vietnam stock market